Effect of ethanol–RON 92 (pertamax) fuel blends on exhaust emissions of a 2000cc gasoline engine - Sudrajad, Agung; Caturwati, Ni Ketut; Sunardi, Sunardi; Khairullah, Adhitya (Politeknik Negeri Lhokseumawe, 2025)
The technology aimed at reducing dependence on fossil fuels and minimizing exhaust emissions involves the use of ethanol as an alternative fuel. This research investigates the effects of blending ethanol with RON 92 (Pertamax) gasoline on the exhaust emissions of a 2000cc four-cylinder gasoline engine. Experiments were conducted using varying ethanol concentrations, and the emissions of carbon monoxide (CO), hydrocarbons (HC), carbon dioxide (CO₂), and oxygen (O₂) were measured and analyzed. Data were presented descriptively and compared. The results indicate that adding ethanol significantly reduces CO and HC emissions. The lowest CO concentration (0.04%) was recorded with a 10% ethanol blend (BE10%), while the lowest HC emission (2316 ppm) occurred at a 15% ethanol blend (BE15%). Conversely, CO₂ emissions increased with ethanol content, peaking at 8.97% for BE15%. These findings demonstrate the potential of ethanol–gasoline blends to lower harmful emissions, particularly CO and HC, while enhancing combustion efficiency, as reflected by the increase in CO₂ levels.